2006
DOI: 10.1152/japplphysiol.00378.2006
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal developmental changes in CO2sensitivity in rats

Abstract: Ventilatory sensitivity to CO(2) in awake adult Brown Norway (BN) rats is 50-75% lower than in adult Sprague-Dawley (SD) and salt-sensitive Dahl S (SS) rats. The purpose of the present study was to test the hypothesis that this difference would be apparent during the development of CO(2) sensitivity. Four litters of each strain were divided into four groups such that rats were exposed to 7% inspired CO(2) for 5 min in a plethysmograph every third day from postnatal day (P) 0 to P21 and again on P29 and P30. Fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
60
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(68 citation statements)
references
References 44 publications
7
60
0
1
Order By: Relevance
“…We found that SC neurons from adult rats had a maintained acidification with a lack of pH i recovery in response to HA, which is similar to what has been found in SC neurons from neonates (23,42), and that the percentage of SC neurons activated or inhibited by HA and the magnitude of these responses were unchanged in adult rats compared with neonates (5). This developmental profile did not coincide with previously described patterns for the development of the rat ventilatory response to hypercapnia (6,49).…”
supporting
confidence: 61%
See 2 more Smart Citations
“…We found that SC neurons from adult rats had a maintained acidification with a lack of pH i recovery in response to HA, which is similar to what has been found in SC neurons from neonates (23,42), and that the percentage of SC neurons activated or inhibited by HA and the magnitude of these responses were unchanged in adult rats compared with neonates (5). This developmental profile did not coincide with previously described patterns for the development of the rat ventilatory response to hypercapnia (6,49).…”
supporting
confidence: 61%
“…It is instructive to compare this pattern of early maturity of chemosensitivity in putative chemosensitive neurons with the early developmental pattern of the whole animal ventilatory response to inspired CO 2 . The exact pattern of this development is uncertain, being either triphasic with a minimum point at about P5-P10 (49) or involving a dramatic increase in the hypercapnic ventilatory response from P15 to P20 (6). Both of these patterns show an increase in the ventilatory response to hypercapnia between P10 and P15 that agrees with the development of chemosensitivity in serotonergic medullary raphé neurons (53).…”
Section: Perspectives and Significancementioning
confidence: 86%
See 1 more Smart Citation
“…The respiratory response to reduced O 2 (hypoxia) or increased CO 2 (hypercapnia) is dependent on the relative size and maturity of the species at birth, and generally increases with postnatal age (Bonora et al, 1994), in part as a result of the increasing sensitivity of both central and peripheral chemoreceptors (Hanson et al, 1989;Davis et al, 2006). In contrast to the adult, the newborn typically does not sustain an increase in minute ventilation (V E ; hyperpnoea) in response to hypoxia, and in some cases V E during hypoxia falls below pre-hypoxic levels (Neubauer et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Despite the reduced breathing in newborns subjected to acute hypoxia, they still hyperventilate because of a larger drop in the rate of oxygen consumption (V O2 ) compared with V E . While the hypercapnic ventilatory response of most newborn species is reduced compared with that of adults Davis et al, 2006), unlike hypoxia, it is sustained over time by a persistent increase in tidal volume (V T ), despite a gradual decline in the initial respiratory frequency (f) increase (Bonora et al, 1994;Cummings and Frappell, 2009). Exceptions to these patterns exist, however, with the neonatal North American opossum (another marsupial) demonstrating an unusually large ventilatory response to hypoxia and a hypometabolic response to hypercapnia (Farber, 1972), which attenuates with age .…”
Section: Introductionmentioning
confidence: 99%